Pembuatan Background Dengan Skema Monokromatik Untuk Membangun Suasana Dramatis Pada Film “Contrast: Two Sided Life” - Nidha, Fatma Qutrotun; Yulianti, Ika; Warman, Rahmat Aditya (Journal of Animation and Games Studies, 2025)
To create a successful animation that is popular with the public, it is necessary to pay attention to various aspects, one of which is the creation of a background. The background helps build the story and atmosphere in an animated film. This study discusses the creation of a visual background with a monochromatic scheme to build a dramatic atmosphere in the animated film "Contrast: Two Sided Life". The monochromatic color scheme is used because it can help strengthen the dramatic scenes in the animated film "Contrast: Two Sided Life" which is a fable animation with a drama and action genre. The design method used is ADDIE (Analyze, Design, Development, Implementation, Evaluation). The result of this design is that the background with a monochromatic scheme is able to help support the story with a more dramatic atmosphere.